Acidogenic fermentation of food waste for production of volatile fatty acids: Bacterial community analysis and semi-continuous operation. (15th May 2020) - Zhang, Le; Loh, Kai-Chee; Dai, Yanjun; Tong, Yen Wah
Graphical abstract: Highlights: Food waste acidogenic fermentation for volatile fatty acids production was studied. The highest total VFAs yield was achieved at initial pH 7.0 at temperature of 35 °C. Classes Clostridia, Bacteroidia and Bacilli dominated functional bacterial species. Feasibility of continuous VFA production was validated using a leachate bed reactor. Average total VFA concentration and yield were 6.3 g COD/L and 0.29 g VFA/g VSadded. Abstract: Acidogenic fermentation of food waste for production of volatile fatty acids (VFAs) contributes to both food waste minimization and resource recovery. To gain knowledge on functional bacterial communities and facilitate continuous production of VFAs, this research firstly studied the effects of initial pH values (i.e. 5, 6 and 7) and temperatures (i.e. 35 °C and 55 °C) on VFAs production, distribution, and bacterial communities during acidogenic fermentation of food waste. The optimal conditions were determined as pH 7 and 35 °C, corresponding to the highest total VFAs yield of 11.8 g COD/L with major components of acetic, propionic and butyric acid. Bioinformatic analysis showed that the relative abundance of the dominant bacterial classes (e.g. Clostridia, Bacteroidia and Bacilli ) were changed by the initial pH values in both mesophilic and thermophilic reactors. NMDS analysis confirmed a significant difference between mesophilic and thermophilic communities. Finally, the feasibility of continuous production and recovery of VFAs was validated using a two-phase leachate bed bioreactor at the optimal conditions. Average concentration and yield of the total VFAs in the continuous operation were 6.3 g COD/L and 0.29 g VFA/g VSadded, respectively. The findings in this study could provide pivotal technical supports for potential pilot- and commercial-scale biorefinery plants for VFAs production from food waste.